Rasch‐built overall disability scale for POEMS syndrome (POEMS‐RODS). Issue 4 (14th October 2022) - Keh, Ryan Yann Shern; Lilleker, James B.; Lavin, Tim; Sive, Jonathan; D'Sa, Shirley; Ramdharry, Gita; Carr, Aisling S.; Lunn, Michael P.
Abstract: Patient‐reported outcome measures engage patients in disease severity measurement and the metrics reported can be meaningful to their lives. The Polyneuropathy, Organomegaly, Endocrinopathy, Monoclonal protein and Skin changes syndrome (POEMS) is a complex multisystem disorder with disabling neuropathy which is distinct from other acquired inflammatory neuropathies. No current POEMS‐specific validated disability scales exist. To address this, we have produced a Rasch‐built overall disability scale (RODS) specific to POEMS. A 146‐item preliminary questionnaire containing relevant activity and participation items for neuropathic disability was applied to 49 clinically stable patients with POEMS from the UK national POEMS cohort. A total of 123 items not fulfilling Rasch model expectations were sequentially removed. The final 23‐item POEMS‐RODS fulfilled Rasch model expectations and showed acceptable test‐retest reliability. The 23‐item POEMS‐RODS is a disease‐specific patient‐reported outcome measure able to detect activity limitations within the range of ability demonstrated by the UK POEMS cohort. Larger international studies are needed to confirm the broader applicability and responsiveness of this scale in other countries.